EXPLORING STUDENTS’ PERCEPTION OF ENGLISH TEACHER STEREOTYPE: THE IMPACT OF TEACHING AND LEARNING ACTIVITIES - Hilya Salasata Nur Faricha; Nazaryo Radja (IKIP Siliwangi, 2022)
This research was conducted with the aim of exploring students' perceptions of the stereotypes of English teachers and their impact on teaching and learning activities. A qualitative approach was used to complete this research. The participants in this study were ninth grade students of the first Islamic high school in Tangerang. The instrument used in this study was a semi-structured interview to answer research questions. The results found in this study were that there were 4 stereotypes in education that emerged based on students' opinions. The first stereotypes that emerge are gender stereotypes; where students prefer to be taught by female teachers than male teachers. This is due to the creation of a comfortable atmosphere when a female teacher teaches. Then the second is age stereotypes; students prefer to be taught by younger teachers than younger ones. Students feel happier because the class atmosphere created is not monotonous like when taught by older teachers. Lastly, racial and religious stereotypes; students do not feel the influence of race and religion so that it does not have an impact on teaching and learning activities. Keywords: Impact, Stereotypes, Students’ Perception, Teaching and Learning Activities